A Role for Iodide and Thyroglobulin in Modulating the Function of Human Immune Cells - Bilal, Mahmood Y.; Dambaeva, Svetlana; Kwak-Kim, Joanne; Gilman-Sachs, Alice; Beaman, Kenneth D. (Frontiers in Immunology, 2017)
Iodine is an essential element required for the function of all organ systems. Although the importance of iodine in thyroid hormone synthesis and reproduction is well known, its direct effects on the immune system are elusive. Human leukocytes expressed mRNA of iodide transporters (NIS, PENDRIN) and thyroid-related proteins (thyroglobulin, thyroid peroxidase). The mRNA levels of PENDRIN and thyroid peroxidase were increased while thyroglobulin transcripts were decreased post PMBC activation. Flow cytometric analysis revealed that both PENDRIN and NIS were expressed on the surface of leukocyte subsets with the highest expression occurring on monocytes and granulocytes. Treatment of leukocytes with sodium iodide (NaI) resulted in significant changes in immunity-related transcriptome with an emphasis on increased chemokine expression as probed with targeted RNASeq. Similarly, treatment of leukocytes with NaI or Lugol’s iodine induced increased protein production of both pro- and anti-inflammatory cytokines. These alterations were not attributed to iodide-induced de-novo thyroid hormone synthesis. However, upon incubation with thyroid-derived thyroglobulin, primary human leukocytes but not Jurkat T cells released thyroxine and triiodothyronine indicating that immune cells could potentially influence thyroid hormone balance. Overall, our studies reveal the novel network between human immune cells and thyroid-related molecules and highlight the importance of iodine in regulating the function of human immune cells.